The Cyclical Pattern of Temporary Layoffs in United States Manufacturing - Lilien, David M. (The Review of Economics and Statistics, 1980)
ONE important question arises out of current attempts to provide a foundation for aggregate wage rigidity and unemployment. How mobile are unemployed workers? Recent theoretical models of unemployment can be divided into two basic categories: the new microeconomic search theories attribute unemployment to the job search and job changing behavior of workers who become permanently separated from their jobs. The newer contract theories attribute unemployment to the periodic employment reductions (via temporary layoffs) that are necessary to accommodate demand fluctuations when workers remain indefinitely attached to specific firms. The relative importance of these two approaches in explaining cyclical unemployment hinges on the share of unemployment over the business cycles that is associated with real labor turnover. Unfortunately no data are currently collected on the fraction of unemployment with or without job change. This paper derives estimates of temporary layoff unemployment for U.S. manufacturing from Bureau of Labor Statistics (BLS) establishment turnover data. After a brief discussion of current unemployment data, a time dependent distributed lag model of manufacturing rehires is developed. The model allows estimation of both the percentage of each month's layoffs that end in rehire and the average duration of unemployment before rehire. Together with the layoff rate, these two statistics determine an estimate of manufacturing unemployment without job change.